Clinical Impact of Saline Volume Infused Through Irrigated-Tip Ablation Catheter in Low Acuity Paroxysmal Atrial Fibrillation Ablation Patients - Chopra, Nagesh (J Atr Fibrillation, 2018)
BACKGROUND: Radio-Frequency ablation (RFA) to achieve pulmonary vein isolation (PVI) remains mainstay therapy for symptomatic paroxysmal atrial fibrillation (PAF). The clinical consequences of large saline infusions during AF ablation have not been systematically studied. We utilized the differential flow-rates of the two commercially available ablation catheters (AC): ‘ThermoCool’ (TCAC) and ‘Surround Flow’ (SFAC) from Biosense-Webster to evaluate the clinical impact of the saline infused in the immediate post-ablation period. METHODS: Consecutive charts of PAF patients between 18 and 81 years who underwent RFA procedure at a tertiary care hospital were reviewed. RESULTS: Forty-seven patients were included in the study (33Males, 65±11years, LVEF 58±7% and left atrial diameter 44±7.5mm, 23TCAC-use). The saline volume infused through the AC was significantly higher with TCAC vs SFAC use (1277±316vs697±299 ml; p<0.001), with no difference in volume infused from other sources, total procedure or RFA times (p>0.05). This led to significant increase in post-ablation weight gain (96±23 vs 97.5±24kg; p=0.002), furosemide usage (39% vs 0%; p=0.0006), urine production (120±79 vs 63±31ml/hr; p=0.003) and post-RFA potassium reduction (4.4±0.42 vs 4±0.32mmol/l; p<0.001) with TCAC use. Significant post-RFA reduction in magnesium, calcium and creatinine, associated hyperchloremic metabolic acidosis and a modest QTc prolongation were also observed with use of both ACs albeit only moderate to weakly correlated with saline volume infused through the AC. No clinical adverse outcomes were encountered. CONCLUSIONS: Higher saline-volume infusing AC use in PAF ablation causes significant post-ablation weight gain despite higher furosemide use, larger urine production and associated post-RFA potassium reduction without increasing morbidity in lower acuity patients. Furthermore, an array of post-ablation electrolyte disturbances causes a modest and clinically insignificant QTc prolongation.